2021
DOI: 10.3390/molecules26071950
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Enzyme-Assisted Extraction and Purification of Flavonoids from Pinus koraiensis Nut-Coated Film and Antioxidant Activity Evaluation

Abstract: Pinus koraiensis nut-coated film is a kind of by-product of nut processing, which has been shown to contain flavonoids, polyphenols, and other substances that can be used to produce natural antioxidant extracts. In this study, response surface methodology (RSM) was used to optimize the extraction process of flavonoids of P. koraiensis nut-coated film (PNF), and macroporous resin HPD600 was used to purify PNF (P-PNF). Its antioxidant activity was examined by DPPH (1,1-diphenyl-2-picrylhydrazyl) radical scavengi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…The maximum extraction rate was 4.78 % at 30 min; lengthy extraction time resulted in a decomposed flavonoid structure. This outcome supported Zhang and his team's findings (M [ 40 ].…”
Section: Resultssupporting
confidence: 86%
“…The maximum extraction rate was 4.78 % at 30 min; lengthy extraction time resulted in a decomposed flavonoid structure. This outcome supported Zhang and his team's findings (M [ 40 ].…”
Section: Resultssupporting
confidence: 86%
“…According to previous studies, the total content of flavonoids increases with increasing temperature because high temperatures cause a decrease in viscosity and surface tension, which ensures better penetration of the solvent into the sample matrix. In addition, it increases molecular motion by accelerating the mass transfer of intracellular bioactive compounds from the plant matrix [36] This is consistent with what was obtained by who found that the optimal temperature for enzyme-assisted extraction and purification of flavonoids from Pinus koraiensis is 55℃ [37]. Therefore, this temperature of 55°C was chosen for obtaining extracts using enzymatic ultrasonic extraction to determine the total flavonoid content in the extracts.…”
Section: Total Flavonoid Content In Extracts Obtained Using Enzyme-as...supporting
confidence: 78%
“…The sample water solutions were then subjected to Sephadex LH-20 column chromatography using a stepwise gradient with a water/ethanol solvent system (ranging from 1/0 to 1/1 to 0/1). Each fraction was collected and concentrated in a rotary evaporator at 45°C to remove the ethanol, and then freeze-dried [ 34 ]. The TPC for each fraction was determined according to the method under 2.3, and the polyphenol purification level was calculated using Formula ( 1 ).…”
Section: Methodsmentioning
confidence: 99%